The Effect of Financial Inclusion on Inflation: Implications from Low and High Financially Developed Economies - Fouda, Rita (AUC Knowledge Fountain, 2025)
This paper studies the effect of financial inclusion on inflation in high and low financially developed countries. The author utilizes country-level annual data of 83 world economies covering the period from 2004 to 2022. The Generalized Method of Moments is utilized to estimate the relationship between six financial inclusion indicators and inflation while combating the endogeneity and heteroskedasticity present in the data. Other macroeconomic variables are added to the model to limit the omitted variables bias. At a second stage, the same relationship is tested using a self-constructed financial inclusion index. The results of the study reveal that when testing the effect of the financial inclusion solely on inflation, as measured by the index, an increase in financial inclusion is associated with an increase in inflation in LFDCs whereas an increase in financial inclusion decreases inflation in HFDCs. The author’s contribution through this paper lays in tackling this specific relationship between financial inclusion and inflation that is still limited in the existing literature. Additionally, this paper studies world economies divided into LFDCs and HFDCs, not a specific country or world region. The author also develops a well-rounded measure for financial inclusion that is built upon the most relevant financial inclusion indicators used in previous studies. Lastly, the paper provides results that could be of great use for policymakers in assessing how their efforts and initiatives in the realm of financial inclusion would impact their ultimate goal, price stability.